2001
DOI: 10.1021/jp0044476
|View full text |Cite
|
Sign up to set email alerts
|

Binding Affinities for a Series of Selective Inhibitors of Gelatinase-A Using Molecular Dynamics with a Linear Interaction Energy Approach

Abstract: The binding of a series of hydroxamate inhibitors with gelatinase-A is examined to evaluate the viability of calculating free energies of binding, ∆G b , utilizing molecular dynamics (MD) simulations with a linear interaction energy approach. In our simulations, a bonded model was used to represent the potentials of the catalytic zinc center. The electrostatic distribution of this model was derived using a two-stage electrostatic potential fitting calculations. The resulting bonded model was then used to gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 50 publications
3
50
0
Order By: Relevance
“…In the current work, the potentials of the catalytic zinc center were represented by a nonbonded model, whereas in our previous work, the bonded model was used. 55 Using those two different potential models, we found that the structures of the catalytic zinc bear some differences, but the obtained LIE models are of similar statistical significance. The bonded or nonbonded models may not be completely correct.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…In the current work, the potentials of the catalytic zinc center were represented by a nonbonded model, whereas in our previous work, the bonded model was used. 55 Using those two different potential models, we found that the structures of the catalytic zinc bear some differences, but the obtained LIE models are of similar statistical significance. The bonded or nonbonded models may not be completely correct.…”
Section: Resultsmentioning
confidence: 87%
“…In our previous work, when adopting the bonded zinc model, the coordinate form of the zinc atom was well-preserved. 55 In the current work, when adopting the nonbonded model, the catalytic zinc is also pentacoordinated, but the coordinate form is different from that in the initial model. Nevertheless, the coordinate form from our MD simulations should be further validated by experiments.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The timeaveraged geometries were used to calculate pertinent ensemble averages after 5, 10, 25, 50, 100, and 200 ps. The respective conformations for the most active ligand (20 , Table 1) after different simulation times are illustrated in Figure 2. In addition to using SASA in Eq.…”
Section: Analysis Of MD Simulation Datamentioning
confidence: 99%